Optimizing performance of semi‐continuous cell culture in an ambr15™ microbioreactor using dynamic flux balance modeling. (30th November 2017) - Kelly, William; Veigne, Sorelle; Li, Xianhua; Subramanian, Shyam Sundar; Huang, Zuyi; Schaefer, Eugene
Abstract : The ambr bioreactors are single‐use microbioreactors for cell line development and process optimization. With operating conditions for large‐scale biopharmaceutical production properly scaled down, microbioreactors such as the ambr15™ can potentially be used to predict the effect of process changes such as modified media or different cell lines. While there have been some recent studies evaluating the ambr15™ technology as a scale‐down model for fed‐batch operations, little has been reported for semi‐continuous or continuous operation. Gassing rates and dilution rates in the ambr15™ were varied in this study to attempt to replicate performance of a perfusion process at the 5 L scale. At both scales, changes to metabolite production and consumption, and cell growth rate and therapeutic protein production were measured. Conditions were identified in the ambr15™ bioreactor that produced metabolic shifts and specific metabolic and protein production rates that are characteristic of the corresponding 5 L perfusion process. A dynamic flux balance (DFB) model was employed to understand and predict the metabolic changes observed. The DFB model predicted trends observed experimentally, including lower specific glucose consumption and a switch from lactate production to consumption when dissolved CO2 was maintained at higher levels in the broth. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 34:420–431, 2018